TBKICHI FUKUSHI, 1894-1991 - IPS, Editor (Indian Phytopathology, 2002)
Teikichi Fukushi, Professor Emeritus of Hokkaido University died on September 4, 1991. He was born in 1894 at Hakodate City, Hokkaido, Japan. He spent 3 years in thepreparatory course in the College of Agriculture, Tohoku Imperial University (later renamed Faculty of Agriculture, Hokkaido Imperial University) in Sapporo andÂ subsequently majored in phytopathology under Professor Kingo Miyabe. In 1919 heÂ graduated and was made a lecturer at this University in 1921. In 1929 he was appointed assistant professor of plant pathology in the Faculty of Agriculture, Hokkaido Imperial University and in 1934 he received the doctorate degree from this University. In 1940 he was promoted to professor. After 30 years’ academic service he retired and wasÂ made emeritus professor in 1958.